Neutrophil Elastase Defects in Congenital Neutropenia - Rydzynska, Zuzanna; Pawlik, Bartlomiej; Krzyzanowski, Damian; Mlynarski, Wojciech; Madzio, Joanna (Frontiers in Immunology, 2021)
Severe congenital neutropenia (SCN) is a rare hematological condition with heterogenous genetic background. Neutrophil elastase (NE) encoded by ELANE gene is mutated in over half of the SCN cases. The role of NE defects in myelocytes maturation arrest in bone marrow is widely investigated; however, the mechanism underlying this phenomenon has still remained unclear. In this review, we sum up the studies exploring mechanisms of neutrophil deficiency, biological role of NE in neutrophil and the effects of ELANE mutation and neutropenia pathogenesis. We also explain the hypotheses presented so far and summarize options of neutropenia therapy.